2010
DOI: 10.1159/000319207
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and the Prevalence of Allergic Diseases, Atopy, and Bronchial Hyperresponsiveness in Korean Adolescents

Abstract: Background: Although several mechanisms underlying the asthma-obesity connection have been proposed, debates still remain. This study was to determine whether overweight is associated with a higher prevalence of atopy, asthma symptoms, airway obstruction, bronchial hyperresponsiveness (BHR) or biomarkers of inflammation in a sample of Korean adolescents. Methods: We conducted a cross-sectional survey involving questionnaires, skin tests, spirometry and methacholine challenge tests among 717 adolescents from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 58 publications
(51 reference statements)
6
39
1
1
Order By: Relevance
“…The explanation for this phenomenon may be found in the results of the study by Johnston et al (23) , who showed enhanced airway responsiveness with attenuation of airway inflammation in obese mice. These observations were confirmed by Yoo et al (24) , who indicated an increased bronchial hyperresponsiveness in obese patients. In addition, at the same time, obesity is associated with increased breathing effort, decreased physical activity and poorer skill performance, which could also cause the development and exacerbation of asthma.…”
Section: Discussionsupporting
confidence: 69%
“…The explanation for this phenomenon may be found in the results of the study by Johnston et al (23) , who showed enhanced airway responsiveness with attenuation of airway inflammation in obese mice. These observations were confirmed by Yoo et al (24) , who indicated an increased bronchial hyperresponsiveness in obese patients. In addition, at the same time, obesity is associated with increased breathing effort, decreased physical activity and poorer skill performance, which could also cause the development and exacerbation of asthma.…”
Section: Discussionsupporting
confidence: 69%
“…Hong et al [68] have reported that high BMI is associated with an increased risk of asthma symptoms in boys. In addition, several studies have indicated an association of obesity with allergic rhinitis and atopic dermatitis in children and adolescents [6970]. …”
Section: Physical and Psychological Comorbiditiesmentioning
confidence: 99%
“…25 Nonetheless, the results are conflicting in the literature. Yoo et al 26 reported that overweight children were more likely to be atopic compared with children with a normal BMI. Atopy also was recently shown to significantly mediate the effect of adiposity on asthma outcomes in Puerto Rican children.…”
Section: Introductionmentioning
confidence: 99%